Management of production risk on objects of machine-building complex - V. S. Serdyuk; A. M. Dobrenko; O. A. Tsorina; E. V. Bakiko (Омский научный вестник)
In order to ensure safe working conditions in mechanical engineering, it is necessary to develop methods of production risks managing in the workplace. The paper proposes an engineering approach based on the use of mathematical models for determining the probability of adverse events in the workplace to develop a methodology for quantitative assessment of production risks for specified processes (operations) at the facilities of the engineering complex. The use of mathematical models makes it possible to uniquely assess changes in the parameters of the technological process in terms of their impact on risk factors, and thus manage the safety of technological processes and improve safety in the workplace.